Prediction of global solar radiation from sunrise hours using regression functions: DOI: 10.48129/kjs.15051 - Haj Ismail, Abd Al Karim (Kuwait Journal of Science, 2022)
The paper estimates the global solar radiation in Dubai and Abu Dhabi meteorological stations in the United Arab Emirates. Theoretical models based on Angstrom-Prescott have been applied on data of sunshine hours for the period from 2010 to 2019. The applied model is validated by comparing the theoretical global insolation of the two stations to the measured values. The performance of the model is tested using statistical indicators such as the coefficient of determination $R^2$ and the Mean Root Square $RMSE$. Theoretical solar radiation estimates the maximum of global solar radiation to be in June for both stations, which is in good agreement with the actual data.